Potential of Entomopathogenic Nematodes for the Control of Plangia graminea (Orthoptera: Tettigoniidae) under Laboratory Conditions - du Preez, F.; Malan, A. P.; Addison, P. (South African Journal of Enology and Viticulture, 2022)
Plangia graminea, locally known as a katydids or “krompokkels”, is a minor pest of vineyards in the Western Cape province of South Africa. Is feed on leaves, and sporadically on the skin of grapevine berries. Under natural conditions, katydids are not of much agricultural importance, but pest outbreaks during favourable conditions can result in significant foliar damage. Observations indicate an increase in katydid abundance and damage intensity in recent years. Currently, no agrochemicals are registered for the control of this species, and its present natural enemies are unlikely to provide sufficient control without augmentation. In this study, 12 entomopathogenic nematode (EPN) species were evaluated against the nymphs of Plangia graminea in laboratory bioassays, and mortality by infection was investigated. Seven locally occurring nematode species achieved significant mortality, with H. zealandica, H. indica, S. jeffreyense and S. yirgalemense being found to perform the best (> 90% mortality).